2008
DOI: 10.1088/0741-3335/50/6/065002
|View full text |Cite
|
Sign up to set email alerts
|

Micropinches in laser induced moderate power vacuum discharge

Abstract: Studies of x-ray emission from a laser induced vacuum discharge of moderate storage energy (<20 J) are examined. It is found that micropinches in the initial stage of the cathode jet expansion into the interelectrode gap are formed. Hot plasma of the micropinches emits a soft x-ray radiation and beams of accelerated electrons moving toward the anode. It is found that these phenomena occur just when both amplitude of the discharge current and energy of the initiating laser pulse lie in the specified ranges of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Such radiation is detected in high-current (with a current of the order of 100 kA), discharges at a voltage of a few tens of kilovolts with stored energy in the kilojoule range, which makes their technological application more difficult. More recent studies have shown that laser-initiated vacuum discharges with a voltage of only a few kilovolts [4][5][6] or even several hundred volts [7] and with a storage energy 10 J can serve as an x-ray source in the energy range 0.5-10 keV. Such discharges, in principle, can be used for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Such radiation is detected in high-current (with a current of the order of 100 kA), discharges at a voltage of a few tens of kilovolts with stored energy in the kilojoule range, which makes their technological application more difficult. More recent studies have shown that laser-initiated vacuum discharges with a voltage of only a few kilovolts [4][5][6] or even several hundred volts [7] and with a storage energy 10 J can serve as an x-ray source in the energy range 0.5-10 keV. Such discharges, in principle, can be used for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown that similar ion beams are also produced with relatively low-voltage vacuum diodes (<20 keV) at a sufficiently high discharge current rise rate exceeding 10 10 A s −1 [7]. It is shown that the appearance of multi-charged ions is due to the formation in the cathodic plasma jet of an area of hot plasma on a micron scale; that is, micropinch [8]. As a reason for the acceleration of ions in the electron beam, it was proposed to capture the ions in a non-steady-state potential well formed by the space charge of the beam [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The emission of soft x-ray radiation from vacuum spark discharge under the focusing of a laser pulse on the cathode is the subject of many publications [1][2][3][4] and recently the theoretical model of such a discharge was developed [5]. What caused our interest to the laser initiation of vacuum spark discharge under the focusing of the laser beam on the anode?…”
Section: Introductionmentioning
confidence: 99%